Prevalence of idiopathic osteosclerosis in patients cared for at a radiological center in Ayacucho from 2016-2018 - Ñahuincopa López, Paul Marcelo (2021)
Objective: The objective of this study was to determine, describe and identify the prevalence of radiopaque images compatible with idiopathic osteosclerosis in digital panoramic radiographs taken in patients between the ages of 18 and 50. Materials and methods: The study design was descriptive, cross-sectional and retrospective. The sample consisted of 500 digital panoramic radiographs taken between January 1, 2016 and December 31, 2018, in the target population aged between 18 and 50 years from Ayacucho - Peru, attended at a private radiological center. The radiographs obtained were analyzed using the Romexis viewer version 5.3 program, and the results were recorded on a data collection sheet. The Chi-square test was used to establish associations among the variables evaluated. A P <0.05 was considered significant. Results: 500 digital panoramic radiographs were analyzed, showing a prevalence of idiopathic osteosclerosis of 17.4%, of which 12% were female and 5.4% male, and according to age, the presence of idiopathic osteosclerosis was more prevalent in the second decade of life. Conclusions: It is important to have a clear differential diagnostic criterion when distinguishing the different radiopacities such as idiopathic osteosclerosis, which can occur in the jaws, making a precise record of the morphometric characteristics and monitoring over time, taking into account their existence and implication in dental treatments.